Pregnancy and miscarriage rates in 3978 donor insemination cycles: Effect of age, parity and partner's infertility status on pregnancy outcome - Gulam Bahadur (2018)
The effects of age, parity and male infertility status on pregnancy outcome were studied in a cohort of 720 women receiving donor insemination (DI) treatment. Twenty-two percent of women failed to complete the treatment, leaving 562 women receiving 3202 cycles of DI for assessment. Of the 321 of pregnancies achieved, 57 (17.8%) ended in a miscarriage. After further DI treatments, 64.7% of mothers who had miscarried succeeded in giving birth. There was some evidence to indicate a trend of decreasing pregnancy rate with increasing maternal age, although this result was not significant (log rank trend statistics = 3.44, P > 0.05). The pregnancy rates of multiparous and primiparous women were significantly different, irrespective of their partner's infertility status (azoospermia: log rank statistics = 3.74, P ≤ 0.05; oligozoospermia: log rank statistics = 4.71, P < 0.03). Furthermore, multiparous women were more likely to become pregnant than primiparous women (azoospermia: hazard ratio = 1.29; oligozoospermia: hazard ratio = 1.50). There was no significant association between miscarriage rate and maternal age (log rank trend statistics = 0.99, P > 0.05). The small number of older women (> 35 years) may confound this result. The mean (± SD) sperm donor age was 23.6 years (± 3.5 years). The implications of these observations are discussed.